Mechanical Forces Accelerate Collagen Digestion by Bacterial Collagenase in Lung Tissue Strips - Yi, Eunice; Sato, Susumu; Takahashi, Ayuko; Parameswaran, Harikrishnan; Blute, Todd A.; Bartolák-Suki, Erzsébet; Suki, Béla (Frontiers in Physiology, 2016)
Most tissues in the body are under mechanical tension, and while enzymes mediate many cellular and extracellular processes, the effects of mechanical forces on enzyme reactions in the native extracellular matrix (ECM) are not fully understood. We hypothesized that physiological levels of mechanical forces are capable of modifying the activity of collagenase, a key remodeling enzyme of the ECM. To test this, lung tissue Young’s modulus and a nonlinearity index characterizing the shape of the stress-strain curve were measured in the presence of bacterial collagenase under static uniaxial strain of 0, 20, 40, and 80%, as well as during cyclic mechanical loading with strain amplitudes of ±10% or ±20% superimposed on 40% static strain, and frequencies of 0.1 or 1Hz. Confocal and electron microscopy was used to determine and quantify changes in ECM structure. Generally, mechanical loading increased the effects of enzyme activity characterized by an irreversible decline in stiffness and tissue deterioration seen on both confocal and electron microscopic images. However, a static strain of 20% provided protection against digestion compared to both higher and lower strains. The decline in stiffness during digestion positively correlated with the increase in equivalent alveolar diameters and negatively correlated with the nonlinearity index. These results suggest that the decline in stiffness results from rupture of collagen followed by load transfer and subsequent rupture of alveolar walls. This study may provide new understanding of the role of collagen degradation in general tissue remodeling and disease progression.